2014
DOI: 10.3906/sag-1301-71
|View full text |Cite
|
Sign up to set email alerts
|

The obesity prevalence among students between the ages of 5 and 19 in Kütahya

Abstract: A new, simple, and rapid cloud point extraction (CPE) procedure system, combined with flame atomic absorption spectrometry (FAAS), was developed for selective separation, preconcentration, and determination of trace amounts of total iron in some environmental samples. The complexing agent, N,N -(2,2 -(ethane-1,2-diylbis(oxy))bis(ethane-2,1-diyl))bis(2-chloroacetamide) (EDBOCA), is selective at pH 5.0 for only Fe(II) and Fe(III) ions in the presence of Cu(II), Pb(II), Cd(II), Mn(II), Co(II), Cr(III), Cr(VI), Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
2
6
0
4
Order By: Relevance
“…Twenty‐seven percent of patients were categorized as overweight or obese, which is similar to that reported in another Turkish study focusing on pediatric psoriasis (28%) . These figures are higher than the overweight and obese percentages in population‐based studies from Turkey (12%‐16%) . More patients who did not describe regular physical activity had a PASI score of 10 or greater.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Twenty‐seven percent of patients were categorized as overweight or obese, which is similar to that reported in another Turkish study focusing on pediatric psoriasis (28%) . These figures are higher than the overweight and obese percentages in population‐based studies from Turkey (12%‐16%) . More patients who did not describe regular physical activity had a PASI score of 10 or greater.…”
Section: Discussionsupporting
confidence: 79%
“…31 These figures are higher than the overweight and obese percentages in population-based studies from Turkey (12%-16%). [38][39][40] More patients who did not describe regular physical activity had a PASI score of 10 or greater. This may be because children with a PASI score of 10 or greater were more likely to abstain from engaging in physical activity with their peers because of distress stemming from the visible nature of psoriatic lesions.…”
Section: Emotions Was the Most Severely Impaired Domain Of Caregivermentioning
confidence: 99%
“…According to previous studies, the rate of cholelithiasis among obese adolescents is 2–6.4% . Obesity prevalence ranges from 3.7% to 4.5% in Turkish school children . In our study, obesity and overweight together was the second most common risk factor.…”
Section: Discussionsupporting
confidence: 57%
“…Several local studies were performed in order to determine obesity prevalence in child and adolescent groups in Turkey (21)(22)(23)(24). Studies conducted in different regions showed that the prevalence of overweight ranged between 8.8% and 12.7% and prevalence of obesity ranged between 1.2% and 6.5% for adolescent girls (21)(22)(23)(24)(25)(26)(27). Recent nationwide study results showed that overweight and obesity prevalence was 12.8% and 8.5% in Turkish adolescent girls aged between 12 and 14 years and between Although the prevalence of obesity (2%) in the present study is low compared to the National Study (4), it has shown compatibility with the results of local studies (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%